Challenges and Opportunities to Recruiting and Engaging with Gay Male Latino Sexual Assault Survivors. Issue 1 (February 2023) - López, Daniel Jacobson; García, Antonio; Engel, Rafael; Jackson, John L.
There is a paucity of empirical literature examining the experiences of gay Latino sexual assault survivors in the United States, due in part because there is little research focused on how to effectively recruit and engage Latino sexual assault survivors as participants in the research process. While researchers have utilized various recruitment methods to engage with gay Latino men, they have not focused specifically on sexual assault survivors. To address this gap, this study examined effective strategies for recruiting and engaging with gay Latino sexual assault survivors. Various recruitment methods were used, and social media-based recruitment methods proved to be the most effective. Researchers need to develop rapport and trust during the screening interview and avoid the risk of re-traumatization.